Packing systems and patterns of physical damage in post-harvest citrus fruit decay in Jammu markets - and M.L. TIKOO, V.S. VERMA (Indian Phytopathology, 2004)
Mandarin oranges (Citrus reticulata) were packed and marketed in wooden boxes with paddy straw as cushioning material whereas kinnow mandarin and acid lime (Citrus aurantifolia) fruits were transported, bulk-packed in gunny bags, to the market. The nature of damage in mandarin was compression bruises and cuts on the fruits. Kinnow mandarin and lime had bruises due to rough handling, compression bruises due to over-filling and over stacking of bags, vibration bruises in transit and storage houses. Besides, Kinnow fruits had stalk puncture wounds. These injuries predisposed the fruits to fungal infections leading to fruit rots. Infections and cullage losses are, therefore, a direct consequence of rough handling and unhygienic storage conditions. A spectrum of post-harvest pathogens caused a variety of fruit rots viz., blue mold rot (Penicillium italicum), green mold rot (Penicillium digitatum, P. chrysogenum), Aspergillus flavus, A. fumigatus rots, black mold rot (Aspergillus niger), core rot (Alternaria alternata, Absidia corymbifera), soft rot (Fusarium moniliforme, Rhizophus stolonifer), stem-end rot (Botryodiplodia theobromae) and sour rot (Geotrichum candidum). Among other pathogens Penicillium spp. inflicted major fruit losses during winter months whereas Aspergillus spp. were responsible for sizeable losses during summer and monsoon months.